Enhancing students’ intercultural communication competence: evidence from an Indonesia–Malaysia partnership program - Athok Fu’adi; Afif Syaiful Mahmudin; Esti Yuli Widayanti; Beta Pujangga Mukti (International Journal of Evaluation and Research in Education (IJERE), 2026)
International community service (ICS) is increasingly recognized as an effective approach for strengthening students’ global and intercultural competence. This study examined the impact of an ICS program conducted between State Islamic University of Kiai Ageng Muhammad Besari Ponorogo and Madrasah Utsmaniyah ABIM Penang, Malaysia, on students’ intercultural communication competence (ICC) and soft skills. Employing a mixed-methods convergent design, the study involved 12 participating students, faculty supervisors, ABIM coordinators, and local community leaders. Quantitative data were obtained through pre–post assessments using validated ICC and soft-skill scales, while qualitative data were collected through interviews, participant observation, and reflective journals. The findings indicate significant improvement across all ICC dimensions, including cultural awareness, sensitivity, communication skills, and reflective competence. Students also demonstrated notable enhancement in soft skills such as leadership, teamwork, adaptability, and empathy, supported by qualitative evidence of increased confidence, communicative flexibility, and ethical awareness during community engagement. Perspectives from supervisors and community stakeholders further corroborated the program’s effectiveness. Overall, the study highlights the value of culturally proximate international service-learning in fostering global competence within Islamic higher education and offers implications for developing sustainable cross-border community service initiatives in the ASEAN context.